Statins for neuroprotection in spontaneous intracerebral hemorrhage. (10th December 2019) - Chen, Ching-Jen; Ding, Dale; Ironside, Natasha; Buell, Thomas J.; Elder, Lori J.; Warren, Amy; Adams, Amy P.; Ratcliffe, Sarah J.; James, Robert F.; Naval, Neeraj S.; Worrall, Bradford B.; Johnston, Karen C.; et al.
Abstract : Statins, a common drug class for treatment of dyslipidemia, may be neuroprotective for spontaneous intracerebral hemorrhage (ICH) by targeting secondary brain injury pathways in the surrounding brain parenchyma. Statin-mediated neuroprotection may stem from downregulation of mevalonate and its derivatives, targeting key cell signaling pathways that control proliferation, adhesion, migration, cytokine production, and reactive oxygen species generation. Preclinical studies have consistently demonstrated the neuroprotective and recovery enhancement effects of statins, including improved neurologic function, reduced cerebral edema, increased angiogenesis and neurogenesis, accelerated hematoma clearance, and decreased inflammatory cell infiltration. Retrospective clinical studies have reported reduced perihematomal edema, lower mortality rates, and improved functional outcomes in patients who were taking statins before ICH. Several clinical studies have also observed lower mortality rates and improved functional outcomes in patients who were continued or initiated on statins after ICH. Subgroup analysis of a previous randomized trial has raised concerns of a potentially elevated risk of recurrent ICH in patients with previous hemorrhagic stroke who are administered statins. However, most statin trials failed to show an association between statin use and increased hemorrhagic stroke risk. Variable statin dosing, statin use in the pre-ICH setting, and selection biases have limited rigorous investigation of the effects of statins on post-ICH outcomes. Future prospective trials are needed to investigate the association between statin use and outcomes in ICH.